Electrochemical preparation system for unique mesoporous hemisphere gold nanoparticles using block copolymer micelles. Issue 14 (28th February 2020) - Lim, Hyunsoo; Nagaura, Tomota; Kim, Minjun; Kani, Kenya; Kim, Jeonghun; Bando, Yoshio; Alshehri, Saad M.; Ahamad, Tansir; You, Jungmok; Na, Jongbeom; Yamauchi, Yusuke
Abstract : Mesoporous hemisphere Au nanoparticles using self-assembled micelles, for the first time, are demonstrated by using electrochemical reduction on a Ti substrate. Abstract : Gold nanoparticles (AuNPs) are widely used in various applications, such as biological delivery, catalysis, and others. In this report, we present a novel synthetic method to prepare mesoporous hemisphere gold nanoparticles (MHAuNPs) via electrochemical reduction reaction with the aid of polymeric micelle assembly as a pore-directing agent.